Anti-Müllerian Hormone promotes human osteoblast differentiation and calcification by modulating osteogenic gene expression - Francesca Liuzzi; Marilena Taggi; Serena De Carlini; Antonio La Marca (Taylor & Francis Group, 2023)
Objective To investigate whether the Anti-Müllerian Hormone (AMH), an ovarian hormone belonging to the Transforming Growth Factor β superfamily, may represent a possible candidate for use as a bone anabolic factor.Methods We performed in vitro studies on Human Osteoblasts (HOb) to evaluate the expression and the functionality of AMHRII, the AMH receptor type-2, and investigate the effects of exogenous AMH exposure on osteogenic gene expression and osteoblast functions.Results We reported the first evidence for the expression and functionality of AMHRII in HOb cells, thus suggesting that osteoblasts may represent a specific target for exogenous AMH treatment. Furthermore, the exposure to AMH exerted a stimulatory effect on HOb cells leading to the activation of osteogenic genes, including the upregulation of osteoblastic transcription factors such as RUNX and OSX, along with increased deposition of mineralized nodules.Conclusion Our findings proved interesting clues on the stimulatory effects of AMH on mature osteoblasts expressing its specific receptor, AMHRII. This study may therefore have translation value in opening the perspective that AMH may be an effective candidate to counteract the bone loss in osteoporotic patients by selectively targeting osteoblast with minimal off-target effect.